Immunogenicity of fowl typhoid vaccine in layer chickens - Ferdous, J; Khan, MSR; Begum, F; Hassan, J (Journal of the Bangladesh Agricultural University, 2010)
The immunogenicity of available fowl typhoid vaccine was studied in layer chickens following usual and suggested schedule of vaccination. A total of 30 chickens were divided into three groups; group A (vaccinated following usual schedule of vaccination), B (vaccinated following suggested schedule of vaccination) and C (as control), each containing 10 layer chickens of Fayoumi breed. Chickens of group A and B were vaccinated with available fowl typhoid vaccine produced by the Governments laboratory at a dose rate of 0.5ml at each occasion through SC route, where 1st dose was administered at 42 days and 35 days of age, respectively, and 2nd dose at 72 days and 65 days of age, respectively. Blood samples were collected to obtain sera from each chicken at every 7 days interval up to 105 days post vaccination for determination of antibody titre following primary and secondary vaccination using microplate agglutination test. The highest mean antibody titre obtained from Group A was 460.8 than that of B was 435.2, respectively. Among the two groups, the highest mean antibody titre of 460.8 was obtained at 56 days post vaccination in group A following usual schedule of vaccination. It revealed that government supplied fowl typhoid vaccine induced higher level of antibody production in both usual and suggested schedule of vaccination. Keywords: Immunogenicity; Fowl Typhoid; Vaccine; Layer chicken; Suggested; Usual DOI: 10.3329/jbau.v7i1.4970 J. Bangladesh Agril. Univ. 7(1): 99-102, 2009